Experiences from a participation process in Göttingen Osterode. Design thinking as a target-oriented method for the participation of young people. - Bradtke, Alexandra (My University, 2020)
Although young people are equal members of the community, they are generally excluded from municipal planning processes. This problem can be resolved by fostering participation, thereby making them more than mere spectators. Young people form a heterogeneous group of individuals who want to be taken seriously, explicitly addressed and motivated. However, it is not easy to reach and motivate youngsters to take part in participatory processes. They frequently have a busy schedule at school, time-consuming leisure activities and long travelling distances in rural areas with inadequate public transport. One approach to sparking the interest of young people, who are constantly online or on their smartphones, is to use the internet. However, methods other than digital participation are required to foster their involvement: We need a dedicated form of participation that takes account of young peoples’ wishes, requirements and ideas in an interesting and attractive way. In the district of Göttingen Osterode am Harz, researchers and regional managers have considered various methods to encourage the participation of teenagers, identifying some concrete results that can be achieved in the target group. In particular, they tested the method of Design Thinking as a form of youth participation. In this paper we consider the background to youth participation and look at how this can be fostered, in particular by investigating the method of Design Thinking. This is found to be successful in motivating young people to get involved in urban design.
Keywords: Mittelstadt; Stadtentwicklungsplanung; Jugend; Planungsbeteiligung; Partizipation; Beteiligungsverfahren; Design Thinking